2004
DOI: 10.1007/s00420-004-0544-z
|View full text |Cite
|
Sign up to set email alerts
|

Gases and organic solvents in urine as biomarkers of occupational exposure: a review

Abstract: A brief review of urine analysis in studies of occupational exposure to volatile organic compounds and gases is provided. Analysis of exhaled breath for volatile compounds does not have a long history in occupational medicine. A number of studies has been undertaken since the 1980s, and the methods are well enough accepted to be put forward as biological equivalents of threshold limit values (TLVs) for some volatile organic compounds (VOCs) such as acetone; methanol; methyl ethyl ketone (MEK); methyl isobutyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 87 publications
1
42
0
1
Order By: Relevance
“…The data on the relationship between VOC concentrations in the air and concentrations of unchanged compounds in blood and for toluene, ethylbenzene, xylene and mesitylene varied from 0.45 h to 0.88 h for phase I and from 6.7 h to 19.2 h for phase II [2]. The data reported recently for exposure in occupational setting show that the determination of unmetabolized solvents in urine provides a highly sensitive and specific index of exposure to VOCs [3][4][5][6][7][8][9][10][11]. The purpose of the present study was to compare the validity of various biomarkers of exposure to toluene, ethylbenzene and xylene at low levels of occupational exposure and to find out whether the determination of unchanged VOCs in urine would be useful for the assessment of exposure around and below the current occupational exposure limit.…”
Section: Resultsmentioning
confidence: 92%
“…The data on the relationship between VOC concentrations in the air and concentrations of unchanged compounds in blood and for toluene, ethylbenzene, xylene and mesitylene varied from 0.45 h to 0.88 h for phase I and from 6.7 h to 19.2 h for phase II [2]. The data reported recently for exposure in occupational setting show that the determination of unmetabolized solvents in urine provides a highly sensitive and specific index of exposure to VOCs [3][4][5][6][7][8][9][10][11]. The purpose of the present study was to compare the validity of various biomarkers of exposure to toluene, ethylbenzene and xylene at low levels of occupational exposure and to find out whether the determination of unchanged VOCs in urine would be useful for the assessment of exposure around and below the current occupational exposure limit.…”
Section: Resultsmentioning
confidence: 92%
“…Benzene was not detected in any sample, regardless the use or not of cigarette by the worker. Although the levels of the solvent in biological fluids of smokers are higher than in the non smokers, concentrations varying between 191-942 ng L -1 in urine 39 and 81-1136 ng L -1 in blood. 40 The LOQ of the method used is higher than its detection in situations of environmental or smoking exposure.…”
Section: Samples From Occupationally Exposed Workersmentioning
confidence: 99%
“…n-Hexane was detected in blood from only two volunteers (33.0 and 41.3 µg L -1 ). Imbriani and coworkers 39,41,42 reported that the urine concentration of unaltered n-hexane corresponding to the TLV-TWA (50 ppm, ACGIH) was 13.09 µg L -1 , not mentioning the corresponding value for blood samples. Although no positive results were obtained for n-hexane in the urine samples from exposed workers, the LOQ established for both fibers permits its use for analysis at concentrations lower than the reported biological limit.…”
Section: Samples From Occupationally Exposed Workersmentioning
confidence: 99%
“…The use was not limited to occupational health where the method was originally developed [1][2][3][4][5][6] , but also in environmental health fields 7,8) . The method has been applied to analysis for un-metabolized mother chemicals 1,[9][10][11][12] as well as for metabolites after proper automated derivatization of metabolites to increase volatility [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%